Emotion Matters: What Happens Between Young Children and Parents in a Touchscreen World. - HOGEUN SEO; SHINHEA LEE, CLAIRE (International Journal of Communication (19328036), 2017)
Young children today are early adopters and frequent users of touchscreen devices. This study explores how parents perceive the role of new media in their families, how and why they regulate children's media use, and how they feel about this process. The study conducts ethnographic interviews with 20 South Korean parents of two- to six-year-olds and observes 10 children in their media use and interaction with parents. We find that parents presumed that touchscreen media wielded a more negative than positive influence on their children. As a result, parents engaged in restrictive and technical mediation, though they often failed to effectively manage their children's media use due to practical challenges. The failure of parental mediation made the parents feel guilty. We suggest a greater need to attend to the contexts and emotions in which parental mediation of children's media use occurs.